Four crops based cropping pattern studies for increasing cropping intensity and productivity in Rajshahi region of Bangladesh - Hossain, I; Mondal, MRI; Islam, MJ; Aziz, MA; Khan, ASM MR; Begum, F (Bangladesh Agronomy Journal, 2015)
A field trial was conducted at the Regional Wheat Research Centre of Bangladesh Agricultural Research Institute (BARI), Rajshahi to study the comparative agronomic performance and economic return of four crops based cropping patterns. The cropping patterns were as follows: CP1= Transplanted Aman rice (cv. Binadhan-7)Mustard (cv. BARI Sarisha14)Boro rice (cv. BRRI dhan28) Transplanted Aus rice (cv. Parija); CP2= T. Aman ricePotato (cv. Diamont)Boro riceT.Aus rice; CP3=T. Aman riceMustard (cv. BARI Sarisha15)Mungbean (cv. BARI Mung 6) T. Aus rice and CP4 = T. Aman riceFallowBoro riceFallow (Control). The results showed that four crops could be grown successfully one after another in a sequence in the field with three crops patterns. The highest rice equivalent yield (REY) 25.62 t ha-1 was obtained from the cropping pattern CP2 (T. Aman ricePotatoBoro riceT.Aus rice) and it was followed by CP1 (18.49) and CP3 (16.03) during one year crops cycle. The highest gross margin Tk. 148882 ha-1 was also obtained from CP2 followed by CP3 (Tk. 133315 ha-1). The highest MBCR (2.24) was however, obtained from the cropping pattern CP3 (T. AmanMustard MungbeanT. Aus). Based on overall yield performance, economic benefit and climatic situation of Rajshahi region it may be concluded that CP3 was the best pattern than others. Bangladesh Agron. J. 2014, 17(2): 55-60